Catching Up or Missing Out? Human Papillomavirus Vaccine Acceptability Among 18- to 26-Year-old Men Who Have Sex With Men in a US National Sample. Issue 11 (November 2015) - Cummings, Teresa; Kasting, Monica L.; Rosenberger, Joshua G.; Rosenthal, Susan L.; Zimet, Gregory D.; Stupiansky, Nathan W.
Abstract : Background: Men who have sex with men (MSM) are disproportionately affected by human papillomavirus (HPV)–related outcomes and would benefit from HPV vaccination in adolescence. We assessed HPV vaccine attitudes, uptake, and barriers in this high-risk young MSM (YMSM) population. Methods: An online US sample of 1457 YMSM aged 18 to 26 years were recruited in December 2011 to examine HPV vaccine acceptability and uptake. The online survey included sociodemographics, HPV vaccine attitudes, acceptability, HPV vaccination status, health care use, and HPV knowledge. Results: Despite high use of health care in the past year (86%) and high acceptability (87.8/100) for free HPV vaccine, only 6.8% had received one or more vaccine doses. In addition, only 4% of unvaccinated men had been offered the vaccine by their health care provider (HCP). In a multivariate regression of unvaccinated men, increased vaccine acceptability was associated with an HCP recommendation, worry about getting infected with HPV, and being tested for a sexually transmitted disease in the past year, whereas safety concerns, lower perceived risk of infection, and shame associated with HPV infection/disease were associated with decreased vaccine acceptability. Through logistic regression, vaccine uptake was associated with being tested for a sexually transmitted disease in the past year, disclosure of being gay or bisexual to a doctor, and greater HPV knowledge. Conclusions: Health care providers need to use routine points of contact with YMSM patients to vaccinate against HPV. These data indicated missed opportunities to vaccinate YMSM who are open to HPV vaccination. In the future, HCPs of YMSM should be careful to avoid missed opportunities to vaccinate. Abstract : A study of young men who have sex with men using a social and sexual networking site for men who have sex with men were found to have high acceptability to human papillomavirus vaccination but low vaccine uptake.